Formalin Itch Test: Low-Dose Formalin Induces Histamine-Independent, TRPA1-Mediated Itch in Mice - Liu, Xu; Zhang, Jiang-Tao; Hu, Yue; Shan, Wen-Qi; Wang, Zhi-Hong; Fu, Qing-Yue; Fu, Dan-Ni; Ji, Jiang; Liu, Tong (Frontiers in Medicine, 2021)
Chronic itch is a common distressing symptom of many diseases, which reduced patient’s quality of life. The mechanistic study on itch and screening for new anti-itch drugs require the development of new preclinical itch animal models. Herein, we established an acute itch model by intradermal (i.d.) injection of low-dose formalin into the neck or cheek in mice. In mice, i.d. injection of formalin (0.1%-5%) in the nape of the neck evoked robust scratching behavior in a dose-dependent manner and the dose-response curves showed an invert “U” shape. I.d. injection of formalin (0.3%-0.6%) into the cheek evoked scratching in mice but wiping in rats, while formalin (1.25%-5%) induced mixed wiping and scratching behavior in both mice and rats. Further, we found that 0.3% formalin-induced scratching was histamine-independent and significantly attenuated by transient receptor potential ion channels A1 (TRPA1) inhibitor (HC030031) or in TRPA1 knockout (KO) mice, but not affected by transient receptor potential ion channels V1 (TRPV1) inhibitor (capsazepine) or in TRPV1 KO mice. Additionally, 0.3% formalin-induced up-regulation of phosphorylation of extracellular regulated protein kinases (p-ERK) in the dorsal root ganglia (DRG) and scratching was suppressed by intrathecal injection of MEK inhibitor U0126 in mice. Incubation of 0.03% formalin induced the accumulation of intracellular reactive oxygen species (ROS) in the cultured DRG-derived cell line ND7-23, and formalin-induced itch was suppressed by antioxidants in mice. Finally, perfusion of 0.03% formalin induced elevation of intracellular calcium in a subset of primary cultured DRG neurons of mice. Thus, these results indicate that low-dose formalin induced non-histaminergic itch by activation of TRPA1 in mice, which may be employed as a useful acute itch model for screening potential anti-itch drugs.